2018
DOI: 10.1590/0004-282x20180016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of direct costs of decompressive craniectomy in victims of traumatic brain injury

Abstract: Decompressive craniectomy for TBI is an expensive procedure that is also associated with high morbidity and mortality. This was the first study performed in a developing country that aimed to evaluate the direct costs. Prevention measures should be a priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…Traumatic brain injury is a major cause of morbidity and mortality, especially in developing countries. 2 Direct traumas generally cause focal lesions, such as epidural hematomas, brain contusions, and skull fractures. 1 The neurosurgery procedures for draining these hematomas, if they have significant repercussion, are well established in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Traumatic brain injury is a major cause of morbidity and mortality, especially in developing countries. 2 Direct traumas generally cause focal lesions, such as epidural hematomas, brain contusions, and skull fractures. 1 The neurosurgery procedures for draining these hematomas, if they have significant repercussion, are well established in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, many huge trials, such as DECRA and RESCUE-ICP, have demonstrated that this procedure has high morbidity and mortality rates. 1,2,9 The technique and indications of DC have been extensively described in previous studies; 4,10 nevertheless, the outcomes and costs are high, and these patients always require at least one more neurosurgical procedure for cranioplasty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, raw cost data was not available in the included studies. However, DC is thought to be an expensive procedure with a mean patient cost of over US$ 20,000 when performed in a developing country [34]. HC is potentially a cheaper alternative due to autologous tissues being utilised and reducing the need for a second operation for a cranioplasty [26].…”
Section: Cost-effectivenessmentioning
confidence: 99%